The Effect of Action Research on Neobladder Function Training in Patients with Orthotopic Ileal Neobladders: A Prospective Cohort Study - Xiao, Chun-Xiu; Zhang, Wei; Lin, Bing-Xin (Urology Journal, 2021)
Purpose: This study aims to evaluate the effects of action research on neobladder function training in patients with orthotopic ileal neobladders. Methods: A total of 68 patients with orthotopic ileal neobladders were randomly divided into two groups: a control group (31 patients) and an experimental group (37 patients). Patients in the control group received neobladder function training, while patients in the experimental group received neobladder function training based on the action research method. The effects of neobladder function training in all patients were evaluated after three months. Results: (1) The differences between the two groups in micturition time interval, urine volume per time, number of incidences of nocturia, and urinary continence rate (day time and night time) were statistically significant (P < 0.05). (2) Compared to the control group (241.6 ± 42.3 mL, 15.1 ± 4.9 mL/s, 23.1 ± 9.9 cmH2O, 63.6 ± 22.3 mL), the bladder capacity (292.6 ± 66.9 mL), maximum urinary flow rate (19.2 ± 6.5 mL/s), and bladder detrusor pressure (31.2 ± 11.4 cmH2O) of the experimental group increased, while the residual urine volume (47.2 ± 21.1 mL) decreased (P < 0.05). Conclusion: Neobladder function training based on the action research method can improve the neobladder function of patients with orthotopic ileal neobladders.